2021
DOI: 10.3389/pore.2021.611088
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Preoperative Magnetic Resonance Imaging in the Evaluation of Myometrial Infiltration and Lymph-Node Metastases in Stage I Endometrial Cancer

Abstract: Purpose: In the developed world, endometrial cancer is one of the most common malignant gynecological cancer types. Due to the highly available diagnostic modalities and patient education, the early detection of the tumor leads to high overall survival.Methods: In this study we analyzed the reliability of preoperative MRI findings in the staging of early stage endometrial cancer, as well as the clinical characteristics of patients underwent radical hysterectomy and the histopathologic evaluation of their tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…PET-CT shows the highest specificity but a moderate sensitivity for detecting lymph node metastasis. The choice of the diagnostic tool (US, CT, PET-CT, MRI) should be made individually according to the patient’s characteristics and imaging accessibility ( Bi et al, 2020 ; Bus et al, 2021 ; Xu et al, 2019 ; Yang et al, 2019 ). Synchronous or metastatic ovarian cancer occurs in 5–29% of patients with endometrial carcinoma, and younger women <45 years of age are five times more likely to have synchronous ovarian cancer than women aged >45 years ( Obermair et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…PET-CT shows the highest specificity but a moderate sensitivity for detecting lymph node metastasis. The choice of the diagnostic tool (US, CT, PET-CT, MRI) should be made individually according to the patient’s characteristics and imaging accessibility ( Bi et al, 2020 ; Bus et al, 2021 ; Xu et al, 2019 ; Yang et al, 2019 ). Synchronous or metastatic ovarian cancer occurs in 5–29% of patients with endometrial carcinoma, and younger women <45 years of age are five times more likely to have synchronous ovarian cancer than women aged >45 years ( Obermair et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, this criterion has a low specificity because hyperplastic nodes can also be enlarged, which may lead to a high percentage of false-positive results. At the same time, it has been demonstrated that nodes with a short axis lower than 1 cm are sometimes proved as metastatic at pathology [24,35].…”
Section: Endometrial Cancermentioning
confidence: 99%
“…In addition, the use of minimal invasive methods will lead to greater potential satisfaction of the patient and the surgeon. This becomes even more important when a hysterectomy is necessary due to the malignant nature of the mass [ 3 ]. More important, the lack of pretreatment suspicion of malignant lesions such as leiomyosarcoma may expose the affected patients to increase the likelihood of intra-peritoneal dissemination as well as distance metastases and in this regard, the demarcation between conservative treatments and invasive surgery is also difficult [ 4 ].…”
Section: Introductionmentioning
confidence: 99%